The Syndrome of External Secretory Function Insufficiency is a Common Complication of Chronic Pancreatitis - Farxodivich, Tolibov Farrux (American Journal of Bioscience and Clinical Integrity, 2024)
Chronic pancreatitis (CP) is a long-term inflammatory disease of the pancreas manifested by irreversible morphological changes that cause pain and/or persistent decrease in function. In CP, morphological changes in the pancreas persist after cessation of the etiological factor.